E-028 Experimental testing of trellix coils in elastase-induced aneurysms in rabbits. (22nd July 2018) - Ding, Y; Dai, D; Herting, S; Boyle, A; Nash, L; Asnafi, S; Jakaitas, D; Johnson, C; Maitland, D; Kallmes, D; Kadirvel, R
Abstract : Purpose: The Trellix (Shape Memory Medical, Inc., Santa Clara, CA) is a new generation shape memory polymer coated coil designed to expand for increased volume filling after implantation. The purpose of this study was to compare the efficacy of the Trellix coil in the rabbit aneurysm model. Methods: Trellix and bare platinum coils were implanted in rabbit elastase-induced aneurysms and followed up at 30 days (n=10 for each group) and 90 days (n=5 for each group). Angiographic aneurysm occlusion was rated as stable, progressive or recanalization. Aneurysm specimen were harvested and subjected to histological studies (H and E staining). Comparisons of angiographic outcome, histologic healing score and neointimal thickness between two groups were performed. Results: The angiographic stable or progressive aneurysm occlusion rate in Trellix group was 4 vs 4 at 30 days and 1 vs 3 at 90 days compared to control group. Mean histologic healing score was not significant between Trellix and control group at 30 days (5.5±2.3 vs 5.9±2.2), but 70% higher in Trellix group at 90 days (7.8±2.1 vs 4.5±2.4). Mean neointima thickness covering the neck was significantly higher in Trellix group at both follow up time points (0.16±0.06 vs 0.05±0.04 mm, p=0.0001 at 30 days; and 0.13±0.02 vs 0.03±0.01 at 90 days, p=0.00001). Microscopic evaluation demonstrated Trellix group at 90 day had high level of connective tissue filled in the aneurysm cavity compared to other groups (figure 1). Conclusion: Trellix coil can promote neointima formation along aneurysm neck, which might be helpful for long term aneurysm healing. Disclosures: Y. Ding: None. D. Dai: None. S. Herting: None. A. Boyle: None. L. Nash: None. S. Asnafi: None. D. Jakaitas: None. C. Johnson: None. D. Maitland: None. D. Kallmes: None. R. Kadirvel: None.